2019
DOI: 10.18551/rjoas.2019-09.03
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of E-Service Quality Toward E-Satisfaction, E-Trust, E-Word of Mouth and Online Repurchase Intention: A Study on the Consumers of the Three-Star Hotels in Lampung

Abstract: The development of business through internet media (e-business) is increasingly prevalent throughout the world. Information and communication technology has also caused borderless relations and caused significant social, economic and cultural changes to occur so quickly. This study aims to examine and explain the effect of electronic service quality on electronic satisfaction, electronic trust, e-word of mouth and online repurchase intention. The survey method was used in this study and for the study sample th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 25 publications
3
18
1
Order By: Relevance
“…This shows that e-service quality can increase customer satisfaction. Previous research has confirmed that there is a positive and significant influence between e-service quality on customer satisfaction (Saodin et al, 2019), (Rita et al, 2019), (Hasman et al, 2019), (Santika & Pramudana, 2018). Research from Lestari & Ellyawati shows that e-service quality has a positive and significant effect on customer satisfaction (Lestari & Ellyawati, 2019).…”
Section: The Influence Of E-service Quality Onmentioning
confidence: 83%
See 4 more Smart Citations
“…This shows that e-service quality can increase customer satisfaction. Previous research has confirmed that there is a positive and significant influence between e-service quality on customer satisfaction (Saodin et al, 2019), (Rita et al, 2019), (Hasman et al, 2019), (Santika & Pramudana, 2018). Research from Lestari & Ellyawati shows that e-service quality has a positive and significant effect on customer satisfaction (Lestari & Ellyawati, 2019).…”
Section: The Influence Of E-service Quality Onmentioning
confidence: 83%
“…E-service quality uses dimensional measurements based on research by Zeithaml et al, which consists of efficiency, reliability, fulfillment, privacy, responsiveness, compensation, and contact (Zeithaml et al, 2002). The next variable is satisfaction which is described based on research from Rita et al (Rita et al, 2019) and online purchase intention using measurements based on research from Saodin et al (Saodin et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations